Analysis of the Effect of Dividend Payout Ratio, Debt to Equity Ratio, and Net Profit Margin on the Stock Price of Technology Companies in Indonesia - Akbar, Muhammad; Nyoman Diana Purnama Sari , Ni (Asian Journal of Social and Humanities, 2026)
The technology sector in Indonesia experienced significant dynamics during the 2020–2024 period, beginning with a surge in stock prices during the COVID-19 pandemic due to accelerated digitalization, followed by a “tech winter” phase in 2022–2023 characterized by declining stock values amid rising interest rates and post-pandemic normalization. This volatility raises questions about the financial factors that influence technology stock prices, particularly given the sector’s unique characteristics of prioritizing growth over immediate profitability. This study aims to determine the effect of dividend payout ratio, debt to equity ratio, and net profit margin on stock prices. The method used in this research is panel data regression. The research data used are financial statement ratios for 2020–2024. The population in this research was 19 technology companies listed on the Indonesia Stock Exchange, with 7 companies sampled and selected by purposive sampling. The analysis technique used in this research is panel data regression, which is processed using the EViews 13 program. The research results using the common effect model indicate that the dividend payout ratio, debt to equity ratio, and net profit margin have no simultaneous effect on stock prices. However, when tested individually, the net profit margin has a significantly positive influence on stock prices, whereas the dividend payout ratio and debt to equity ratio do not have any significant effect.